WHAT IS CORPUS LINGUISTICS? (World Bulletin of Social Sciences, 2024)
The goal of this article is to give explicit information on definitions of corpus linguistics, electronic linguistic corpus, and corpus technologies. A brief historical background on the development of corpora and corpus linguistics was given. Morover, the types and advantages of corpora were discussed.
Keywords: corpus linguistics; corpora; text; representativeness